2016
DOI: 10.3390/proteomes4040035
|View full text |Cite
|
Sign up to set email alerts
|

The Proteome of the Red Blood Cell: An Auspicious Source of New Insights into Membrane-Centered Regulation of Homeostasis

Abstract: During the past decade, the hand-in-hand development of biotechnology and bioinformatics has enabled a view of the function of the red blood cell that surpasses the supply of oxygen and removal of carbon dioxide. Comparative proteomic inventories have yielded new clues to the processes that regulate membrane–cytoskeleton interactions in health and disease, and to the ways by which red blood cells communicate with their environment. In addition, proteomic data have revealed the possibility that many, hitherto u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Physiological aging in vivo , as well as aging in vitro during storage in the blood bank, induces changes in the red cell membrane ( 7 ), in the activity of the main metabolic pathways ( 8 , 9 ), and in hemoglobin ( 10 ). These changes not only affect function by decreasing deformability ( 11 , 12 ), but also lead to the appearance of signals that trigger recognition and removal by the immune system.…”
Section: Red Blood Cell Agingmentioning
confidence: 99%
“…Physiological aging in vivo , as well as aging in vitro during storage in the blood bank, induces changes in the red cell membrane ( 7 ), in the activity of the main metabolic pathways ( 8 , 9 ), and in hemoglobin ( 10 ). These changes not only affect function by decreasing deformability ( 11 , 12 ), but also lead to the appearance of signals that trigger recognition and removal by the immune system.…”
Section: Red Blood Cell Agingmentioning
confidence: 99%
“…Increased vesiculation is associated with systemic inflammation, which may be directly responsible for hemolysis and anemia ( Dinkla et al, 2012b , 2016 ). Thus, microvesicles are part of the complex of interactions between RBCs and the organism ( Bosman, 2016a , b ). In this review, we aim to integrate the newest data on microvesicle composition and production in various conditions, in order to obtain more insight into the basic mechanisms underlying microvesicle generation, and the involvement of RBC-derived microvesicles in pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…A recent, in depth quantitative analysis of the RBC proteome, identified 2650 proteins, 1890 of them occurring at more than 100 copies per cell, findings which were validated by a targeted analysis using labelled standards and which can serve as a useful tool for further studies on RBC pathologies and aging [30]. Comparative proteomic inventories of RBC membrane have yielded new clues to the mechanisms regulating membrane-cytoskeleton interactions in health and disease, and to the ways by which erythrocytes communicate with their environment [31]. In addition, proteomic data have indicated that many, hitherto unsuspected, metabolic processes may be active in the RBC cytoplasm [31], as suggested by the presence of new receptor/signaling pathways, stress proteins, transport systems, and proteases [28,32].…”
Section: Red Blood Cellmentioning
confidence: 90%
“…Comparative proteomic inventories of RBC membrane have yielded new clues to the mechanisms regulating membrane-cytoskeleton interactions in health and disease, and to the ways by which erythrocytes communicate with their environment [31]. In addition, proteomic data have indicated that many, hitherto unsuspected, metabolic processes may be active in the RBC cytoplasm [31], as suggested by the presence of new receptor/signaling pathways, stress proteins, transport systems, and proteases [28,32]. Interestingly, erythrocyte metabolism does not seem to be restricted to energy production and redox status, since amino acid and lipid metabolism may be particularly active as well [33,34].…”
Section: Red Blood Cellmentioning
confidence: 99%